Association of Libido with Serum Hormone Profile and Semen Quality in Breeding Buffalo Bulls - Singh Sidhu, Tanvir; Kumar, Ajeet; Honparkhe, Mrigank; Kumar Singh, Ashwani; Singh, Narinder (The Indian Journal of Animal Reproduction, 2025)
The libido of buffalo bulls is crucial factor for influencing the semen production for artificial insemination programs. The present study investigated the relationship of libido with hormonal profiles and semen quality of Murrah (n = 5) and Nili Ravi (n =1) buffalo bulls classified into good (n = 2), average (n = 2) and poor (n = 2) libido groups based on reac tion time (< 3 min, between 3-6 min and > 6 min, respectively). Serum testosterone, estradiol, prolactin and kisspeptin levels were assayed post-GnRH administration using ELISA kits, while serum nitric oxide (NO) was assayed using Griess reaction kit (ELISA kit). Fresh semen quality (volume, concentration, total motility) and post-thaw frozen semen qual ity, including CASA-derived motion traits and morphological parameters, were evaluated. Serum testosterone, estradiol, prolactin kisspeptin and NO didn’t significantly differ across libido groups, however testosterone to estradiol (T/E) ratio was significantly higher in bulls exhibiting good libido traits (p < 0.05). Among hormones, solely kisspeptin and T/E ratio showed significant positive correlation with each other. Fresh semen parameters (volume, sperm concentration and fresh motility) were significantly superior in the good libido buffalo bulls (p < 0.01). For post-thaw semen, motility parameters were similar across groups, while several kinetic motion traits (DCL, DSL, DAP, VCL, VSL, VAP, radius, ALH, HAC) were significantly higher in good libido group (p < 0.01). Sperm viability, acrosomal integrity, and mito chondrial membrane potential didn’t differ significantly (p > 0.05). Evaluating correlation among serum hormones and semen quality, T/E ratio showed significant (p < 0.05) correlation with DCL, DSL, DAP and VSL, while relation among other parameters remained non-significant (p > 0.05). In conclusion, good libido of buffalo bulls positively influences their semen quality. Among serum hormones, T/E ratio influences the libido exhibition in buffalo bulls